Efficacy of intraoperative epidural dexamethasone and bupivacaine in reduction of pain and disability following lumbar discectomy - Reza Saebi; Aidin Shakeri; Alireza Mohammadi; Mohsen Dalvandi; Alireza Kamali (Journal of Family Medicine and Primary Care, 2022)
Background: In lumbar disc herniation, although surgery can provide relief from pain in the low back and lower extremities, many drugs can provide more relief; thus, the aim was the evaluation of epidural dexamethasone and bupivacaine efficacy in lumbar disc herniation surgery. Methods: A total of 42 cases were evaluated in a triple-blind randomized clinical trial study. Patients were divided into intervention and control groups based on permuted block randomization. The patient's condition was assessed based on the Visual Analogue Scale (VAS) at 3, 6, 12, and 24 h and 1, 3, and 6 months after surgery. In addition, the patient's disability was assessed by Oswestry disability index (ODI) at 1 and 6 months after surgery. Results: Of the 42 evaluated cases, age (44.0 ± 12.4, P = 0.4) and hospitalization duration (1.9 ± 0.3 days, P = 0.02) had statistically significant difference between two groups. The severity of low back pain before surgery was 2.9 ± 1.9 (P = 0.74), and 3 hours after surgery was 4.9 ± 1.9 in the control group and 2.8 ± 1.3 in the intervention group (P = 0.03), and there was a statistically significant difference between the two groups. In addition, based on the repeated measure test, there was no significant difference between the two groups. ODI value was before surgery 31.7 ± 8.3 (P = 0.77), 5.2 ± 2.4 (P = 0.9) at 1 month after surgery, and 4.5 ± 1.8 (P = 0.6) at 6 months after surgery, and there was no statistically significant difference between the two groups. Conclusion: Dexamethasone and bupivacaine can be effective in post-operation pain control, although this difference between the two groups was not statistically significant.